Tex Morton interviewed by Jack Munting for his Tasmanian radio programme in the 1960's in Rob and Olya Willis folklore collection - Morton, Tex, 1916-1983.; Willis, Rob, 1944-; Willis, Olya.; Munting, Jack, 1925-2007. (1960)
Folkloric recording. The interview covers why Tex Morton was in Tasmania at the time of the radio interview and talks about his career over the last 10 years. The interview gives an insight into Tex's promotional style.
Music and singing: May I sleep in your barn tonight mister? (Tex played the guitar and sang this song during the radio interview but the performance itself has been deleted from this recording)
Dubbed from the original recording by Rob and Olya Willis on May 10, 1999 with the permission of Jack Munting.
Radio programme originally recorded in 1960 at Launceston, Tas.
Digital master available
Quality of recording variable.
Keywords: Morton, Tex, -- 1916-1983.; Country musicians -- Australia -- Interviews; Radio programs -- Tasmania; Country musicians